The Effect of Atmospheric Pressure Variations on the Suprapermafrost Groundwater Level and Runoff of Small Rivers in the Anadyr Lowlands, Northeast Russia - Oleg D. Tregubov; Boris I. Gartsman; Vladimir V. Shamov; Lyudmila S. Lebedeva; Anna M. Tarbeeva (Water, 2022)
The present-day models of the hydrological regime of soils and river basins do not include a hypothesis regarding the effect of atmospheric pressure on hydrological processes (baric effect), which is assumed negligible. However, their manifestations are likely, considering the mechanical and hydrophysical properties of shallow peat-bog soils (plasticity and elasticity, high moisture-retention capacity, the ability to swell and shrink) and the important role of undecomposed plant remains. The effect of atmospheric pressure variations on level changes in a suprapermafrost aquifer was detected using field and laboratory experiments in shallow peat and peaty tundra soils in the Anadyr Lowlands, Northeast Russia. One can see this effect in the runoff regime of 1st–4th orders streams. The manifestations of this phenomenon can differ, and in particular, they can be directed oppositely. The changes in the level and storage of suprapermafrost gravitational water could be caused only by synchronous (in phase opposition) changes in capillary water fringe above the groundwater table. To explain the observed phenomena, a conceptual model is developed based on the analysis of the balance of forces and water balance in a system of elastic capillaries. Not being complete and perfect, the model reproduces qualitatively the main observed cases of the response to air pressure changes, proving the effect itself, and suggests the likely localization of its mechanisms. A shallow suprapermafrost groundwater table in contact with the peat bottom, as well as incomplete (below the full moisture capacity) water saturation of peat soil horizons, appear to be circumstances of the baric effect on tundra shallow subsurface aquifers. Favorable conditions for the baric effect in a soil profile include a high elasticity of peat-soil matrix, high and variable values of porosity and water yield of peat and moss cover, and, at the catchment scale, a high proportion of coverage by these types of soils. A full-scale study of a mechanism of baric ...